\(A=\frac{1}{1.2}+\frac{1}{2.3}+...+\frac{1}{2019.2020}\)
\(=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{2019}-\frac{1}{2020}\)
\(=1-\frac{1}{2020}< 1\)
\(\Rightarrow A< 1\left(đpcm\right)\)
\(A=1-\frac{1}{2}+\frac{1}{2}-...+\frac{1}{2019}-\frac{1}{2020}\)
\(A=1-\frac{1}{2020}\)
\(=>ĐPCM\)
Ta chứng minh được \(\frac{1}{m\left(m+1\right)}=\frac{m+1-m}{m\left(m+1\right)}=\frac{m+1}{m\left(m+1\right)}-\frac{m}{m\left(m+1\right)}=\frac{1}{m}-\frac{1}{m+1}\)
Ta có \(\frac{1}{1.2}=1-\frac{1}{2}\)
\(\frac{1}{2.3}=\frac{1}{2}-\frac{1}{3}\)
.....
\(\frac{1}{2019.2020}=\frac{1}{2019}-\frac{1}{2020}\)
=> \(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{2019.2020}\)\(=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{2019}-\frac{1}{2020}\)
=>\(A=1-\frac{1}{2020}< 1\)
Vậy \(A< 1\)
Ta có:
A = \(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+....+\frac{1}{2019.2020}\)
A = \(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+....+\frac{1}{2019}-\frac{1}{2020}\)
A = \(1-\frac{1}{2020}\)
A = \(\frac{2019}{2020}\) < 1